PENGARUH pH TERHADAP SENYAWA ANTIOKSIDAN DAN KEMAMPUAN ANTIOKSIDAN BERAS MERAH ENDE VARIETAS ARE NDOTA DAN PARE LAKA - Sigi, Merlina S; Aspatria, Utma; Lalel, Herianus J.D. (Pergizi Pangan DPD NTT, 2011)
Are Ndota and Pare Laka red rice are good source of food antioxidant. The processing including acid or base treatment can influence the compounds and the ability of red rice antioxidant. This study aims to determine the effect of pH on antioxidant compounds and antioxidant capacity of Ende red rice varieties Are Ndota and Pare Laka. This research using completely randomized design with eleven treatments and two replication. Anthocyanin content was tested by using spectrophotometric method, the phenol content was tested by using Folin-Ciocalteu method, the ability to capture the free radicals was tested by using the Kim method and the protective power by using Thiocyanate method. The statistical result tests on the anthocyanin content of both types of red rice showed no significant different (P≥ 0.05) among the eleven treatment, but the phenol content of red rice Pare Laka was significant different (P≥ 0.05) among the eleven treatments. The ability of free radicals from both types of red rice showed no significant (P≤0.05) among the eleven treatments, ability protective power for five days from Are Ndota rice, showed no significant difference (P≥0.05).